Pengaruh Taman Bacaan Masyarakat Spirit (Books & Coffee) Medan terhadap Minat Baca Masyarakat - Yusniah Yusniah; Dinda R. A. Hasibuan; Adha Rahimi; Nisya Siregar; Sri Ulina (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
The study's objective was to ascertain how the SPIRIT (Books & Coffee) Medan community reading park affected people's interest in reading.The goal of this study is to find out how the SPIRIT (Books & Coffee) Medan community reading park affects people's interest in reading.This study utilized a qualitative research approach, specifically direct observation and interviews.This study found that TBM serves as a center for innovative community activities, a reading resource center, and a community learning center.This institution was established to foster a love of reading among the community.The manager of SPIRIT (Books & Coffee), Medan, who's goal is to get people interested in reading, backs it. Keywords: Reading Garden,TBM